(untitled) (Scientific journal of the Fergana State University, 2025)
In the article, it is noted that soil fertility decreases year by year as a result of erosion, degradation and dehumification processes, that agrochemical maps are not followed in the application of mineral fertilizers, it is necessary to pay attention to organic fertilizers in increasing soil fertility, and humus is the most important factor in increasing soil fertility.